Peer Review and Corrective Feedback to Improve the Quality of Students' Article Writing - Budiharso, Teguh (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
The purpose of this study was to analyze the effect of peer review and corrective feedback on the quality of scientific article writing of the students, either partially or simultaneously. The research design was a correlation. The research sample was 85 English education students at Mulawarman Samarinda. The process of collecting data was a survey method with the help of google forms. Data analysis was operated using SPSS application. Results show the following. First, there is a significant effect of peer review on the quality of student scientific writing with an R2 of 0.392. Peer review contributes to the quality of student scientific papers by 39.2%. Second, corrective feedback has a significant effect on the quality of student scientific writing, with an R2 of 0.615. This means that corrective feedback has an effect of 61.5% on improving the quality of student scientific work. Third, there is an effect of peer review and corrective feedback together on the quality of student scientific writing with an R2 of 0.638. This means that peer review and corrective feedback together contribute to the quality of student writing by 63.8%.